Photovoltaic Solar Energy as a Power Source for Coal Waste Measurement Equipment - Nurhalim Dani Ali; Feranita Feranita; Yoga Pratama; Noveri Lysbetti Marpaung; Iswadi Hasyim Rosma; Suwitno Suwitno (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
Coal mines are generally located in very remote areas and so far from the reach of the power grid. This study designs a coal waste measurement device using solar energy as the power source. The parameter being measured for coal waste is its acidity level to determine water quality standards. The test results show that the photovoltaic (PV) system is capable of supplying power to the pH meter device for a duration of 24 hours with a battery capacity of 18 Ah. The total load of this system is 5.6983 Watts. With variations in load and different weather conditions such as clear, cloudy, and overcast, the solar panel voltage can effectively meet the load requirements within the voltage range of 16.7 volts to 20.9 volts.